2020
DOI: 10.1177/0003134820939944
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a 31-Gene Expression Profile Into Clinical Decision-Making in the Treatment of Cutaneous Melanoma

Abstract: Background The practice of utilizing gene expression profile (GEP) for the evaluation and treatment of cutaneous melanomas has been found to predict the risk of sentinel-node metastasis and recurrence. Information obtained from this assay has been used to determine clinical decision-making, including serving as an indication for sentinel lymph node biopsy and also for the intensity of screening measures. Methods Herein we present our early experience in utilizing 31-GEP in intermediate melanomas and its effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Furthermore, approximately 65% of class 1 results lead to surveillance intensity similar to AJCC8 stage I-IIA, while 98% of class 2 results lead to increased scrutiny, similar to patients with AJCC8 stage IIB-IV CM [64]. Overall, studies have found that 31-GEP class results had the potential to positively influence management decisions among physicians [63][64][65] and nonphysician providers [66], consistent with the augmented risk stratification provided by GEP testing.…”
Section: -Gep Testmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, approximately 65% of class 1 results lead to surveillance intensity similar to AJCC8 stage I-IIA, while 98% of class 2 results lead to increased scrutiny, similar to patients with AJCC8 stage IIB-IV CM [64]. Overall, studies have found that 31-GEP class results had the potential to positively influence management decisions among physicians [63][64][65] and nonphysician providers [66], consistent with the augmented risk stratification provided by GEP testing.…”
Section: -Gep Testmentioning
confidence: 76%
“…[36,[39][40][41][42]50]. Studies also suggest that GEP tests may provide more nuanced information to assist dermatologists in managing CM with regards to SLNBx in conjunction with current NCCN guidelines [37,38,43,46,49,54] and potentially reduce unnecessary testing, procedures, and annual healthcare expenditures [28,[60][61][62][63][64][65][66]. While meta-analyses are not yet available for all prognostic CM GEP tests, two recent separate studies [49,67] found similar and robust evidence for the 31-GEP test, which was also supported by clinical recommendations (including A-strength recommendations for the use of the 31-GEP to guide management of patients with negative SLNBx) from an independent consensus panel [10].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that clinicians combine 31-GEP results with other factors to align management plans with patient risk. [26][27][28] No DISCUSSION Table 3. Reclassification of risk in patients with 5-10% SLN positivity risk ("consider" SLNB; T1aHR-T1b) for whom SLNB guidance is not definitive Limitations of this study include its retrospective nature and that this selected population from primarily surgical centers may not represent the general population.…”
Section: Skinmentioning
confidence: 99%